2022
DOI: 10.1186/s40794-022-00173-7
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of researchers in Arab countries to scientific publications on neglected tropical diseases (1971 – 2020)

Abstract: Background The neglected tropical diseases (NTDs) are endemic in several Arab countries. The purpose of the current study was to assess the contribution of researchers in Arab countries to the knowledge base on NTDs using bibliometric indicators. Methods Keywords related to all 20 NTDs were obtained from previously published bibliometric studies and were combined with the names of Arab countries listed as country affiliation. the search strategy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The data of this study were derived from the Scopus database. For numerous reasons, the current analysis was performed using the SciVerse Scopus database [34][35][36]. First, compared to other databases such as PubMed or Web of Science, Scopus has a much larger number and diversity of indexed publications.…”
Section: Sources Of Literature Datamentioning
confidence: 99%
“…The data of this study were derived from the Scopus database. For numerous reasons, the current analysis was performed using the SciVerse Scopus database [34][35][36]. First, compared to other databases such as PubMed or Web of Science, Scopus has a much larger number and diversity of indexed publications.…”
Section: Sources Of Literature Datamentioning
confidence: 99%
“…Indeed, international collaboration has proven to increase the quantity and quality of research activity, as well as the visibility of scientific production in the Arab region (36). In addition to international collaborations, research collaboration among Arab countries is pivotal to facilitate the exchange of experience and knowledge in the region (37). Finally, the findings of this study also revealed that most of the author's keywords and the titles co-occurrence do not mention terms related to early screening, diagnosis, and treatment, reflecting the need to pool more resources and build capacity for increased clinical-based studies.…”
Section: Discussionmentioning
confidence: 85%
“…It is therefore essential to promote economic investments, structures, and collaborative initiatives to foster research in the geographical areas and low- to middle-income countries where the disease has the largest impact. Such initiatives are relevant both in the case of cysticercosis and neurocysticercosis, analyzed in the present study, and more broadly for the rest of the NTDs ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%